Discourse network of a public issue debate: a study on Covid-19 cases in Indonesia - Eriyanto; Ali, Denny Januar (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research is intended to answer the question of the discourses developed in association with Covid-19 management. Discourse in this regard is understood within the context of public policy, i.e. a set of concepts or ideas conveyed by actors to influence public policies. This study employed a discourse coalition theory. In addition, this study applied a discourse network analysis (DNA) method, combining discourse analysis (qualitative contents) and social network method. The DNA method maps any developing discourses on an issue (what) and also actors stating such discourses (who). The research was carried out for five months, starting from 17th November 2019 to 30th April 2020 and it included 1,123 statements of actors that were published in the media. The results of this study show that a coalition of discourse also occurs in health issues. The study reinforces the findings of Leifeld and Haunss (2011) on how actors attempt to present discourse to dominate the public conversation. This research shows the efforts of government actors, i.e. central government, regional governments, and the Ministry of Health, to conduct a coalition between two opposing discourses. The government efforts are not entirely successful. The government is also less successful in using communication channels and social media to form a single discourse.